Perbedaan abnormal return dan volume perdagangan saham sebelum dan sesudah adanya sanksi regulator - Nurachman, Dwi Aditya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze and empirically demonstrate the difference in average abnormal returns before and after the announcement of the PT Sunprima Nusantara Pemfundan event, and to show the difference between the average stock trading volume activity before the event and empirical tests and evidence after the event. event. PT Sunprima Nusantara funding. Applied Research Methods The methods in this study are validation methods, ie. H. A study designed to determine the relationship between a variable and other variables. The method is performed by testing hypotheses and answering question formulas through data collection. This study employs a quantitative approach by testing the event research theory of information content, namely OJK KAP sanctioning Deloitte for not paying PT SNP Finance for events. Based on the results of the research and discussion, the authors concluded that abnormal returns for companies using KAP services sponsored by KAP Deloitte decreased on average after the official sanctions came into effect on October 1. However, statistical tests showed no significant difference in the share prices of companies using KAP Deloitte-sponsored KAP services before and after regulatory sanctions. This means that sanctions imposed by regulators will not have a significant impact on the share prices of companies that use KAP's services under the auspices of KAP Deloitte.